Market Environment, Trade Technology, and Migrants' Performance - Oded Stark (Migration: A Challenge for Europe. Symposium 1993, 1994)
This paper is motivated by an attempt to account for the empirical finding that quite often migrants outperform the native-born. The underlying idea is that how migrants fare, absolutely and relative to the indigenous population, depends on group attributes ratber than on individual abilities and skills. lt is postulated that characteristics of the market environment and trade technology, rather than returns to traditional characteristics of human capital, play a role in explaining this outcome.
Keywords: F22; J24; 330; migration; human capital